(untitled) (Research, Society and Development, 2022)
This is a descriptive study that aimed to analyze the opinions of Physical Education students about the influence of remote teaching on the development of Course Completion Works. An online questionnaire was applied to 32 students (53.12% male, mean age of 26.59 ± 5.01 years, 56.2% with a monthly income of up to 2 minimum wages), where the responses were analyzed and categorized to identify key inferences. The students brought different perspectives on several factors such as the main benefits and difficulties of the construction of the Course Completion Work in the remote teaching model, and the interference of technological support and the conditions of the home environment. It was concluded that remote teaching in the face of social distance was seen by the group of students as a facilitator due to the optimization of time, absence of displacements and ease to carry out the collections, however, it also brought difficulties in communication and access to technologies.